PENINGKATAN HASIL BELAJAR DENGAN MENGUNAKAN MEDIA VIDEO PEMBELAJARAN PADA MATA PELAJARAN TEMATIK DI SEKOLAH DASAR - Septiana, Dinnuriska; Tisnasari, Sundawati; Permana, Ridwan Hadi (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2024)
This research was conducted with the aim of knowing the increase in learning outcomes through the use of video media in thematic learning in class III SDN 3 Keusik, Banjarsari District, Lebak Regency. The method used in this research is Classroom Action Research which aims to overcome the problems that exist in the classroom. The research was conducted in two cycles, and at the end of each cycle a reflection was made on the actions taken. To collect data, observation techniques, questionnaires, and documentation were used. The results showed that the implementation of learning using video media in thematic learning was able to increase students' learning motivation. The research subjects consisted of 15 class III students. It can be seen that the increase in students' learning motivation has increased from cycle I of 62 with a total of 11 people or 73% completion. In cycle II the average student learning outcomes is 76 with 100% of students completing. Thus, it is proven that the use of video media in thematic learning is effective in improving student learning outcomes. Keywords: Learning Outcomes, Learning Media, Video